Eligibility for faricimab in a real-world diabetic macular oedema population: a cross-sectional study - Helena Norberg; Inger Westborg; Ayat Al-Najjar (BMJ Open)
Purpose To investigate the eligibility for faricimab in a real-world diabetic macular oedema (DMO) population to the YOSEMITE and RHINE trials, and to compare the eligible DMO populations to the trial populations.Design, settings and participants This retrospective cross-sectional analysis used data from the Swedish Macula Registry (SMR) between 1 January 2019 and 31 August 2023. Eligibility criteria mirrored the main criteria of the YOSEMITE and RHINE trials: (1) DMO diagnosis, (2) treatment-naïve, (3) 18 years or older, (4) central retinal thickness (CRT) 325 µm or higher and (5) best-corrected visual acuity (BCVA) ranging from 25 to 73 letters. Individuals with registered proliferative diabetic retinopathy (DR) at the start of treatment were excluded. A secondary selection of eligible individuals was conducted using the same criteria, except for BCVA, which ranged from 25 to 77 letters according to national guidelines (treatment practice).Main outcome measures Characteristics at the initial visit of the two eligible SMR populations were compared with baseline data from the clinical trials, respectively.Results In total, 3777 individuals with DMO were selected from SMR. Of these, 2357 (62.4%) individuals were treatment-naïve, all were 18 years or older, 1928 (51.0%) exhibited CRT≥325 µm, 1175 (31.1%) had 25–73 letters based on phase III studies, while 1528 (40.5%) had 25–77 letters according to treatment practice. After excluding individuals with registered proliferative DR 1171 (31.0%) individuals in the SMR met all criteria based on phase III studies, while 1522 (40.3%) individuals fulfilled the criteria according to treatment practice. The SMR and treatment practice populations were older (YOSEMITE 67.5±11.6 vs 62.8±10.0 years, p<0.001 and RHINE 67.5±11.6 vs 61.6±10.1 years, p<0.001) than those in the phase III studies and had lower CRT (YOSEMITE 446±96 vs 486±131 µm, p<0.001 and RHINE 446±96 vs 471±127 µm, p=0.001).Conclusion Approximately 30% of DMO patients in the SMR met the main trial criteria from YOSEMITE and RHINE, while around 40% met the criteria based on treatment practice. The SMR and treatment practice cohorts were older and had less severe DMO than the trial cohorts. Further research into the safety profile of faricimab in clinical settings is necessary, along with the consideration of additional eligibility criteria when implementing faricimab in ophthalmology practice.